Animation and interactivity facilitate acquisition of pediatric life support skills: a randomized controlled trial using virtual patients versus video instruction - Lehmann, Ronny; Lutz, Thomas; Helling-Bakki, Astrid (BMC medical education, 2019)
Several promising studies suggest a positive impact of interactive and media-enriched e-learning resources such as virtual patients (VP) on skill acquisition in pediatric basic life support (PBLS). This study investigates which immanent VP components account for this effect.